Digital Marketing Adoption in SMEs: A Technology-Organization-Environment (TOE)-Based Assessment of Business Growth and Competitiveness - May, Eyeregba Equitozia; Bunmi, Eboesomi Esther; Oyekunle, David Oyewumi; Ugbomeh, Williams Ogochukwu; Matthew, Ugochukwu Okwudili (Recent Research Reviews Journal, 2025)
Adopting digital marketing approaches has emerged as a key factor in Small and medium-sized enterprises (SMEs) competitive advantage and business success. The Technology-Organization-Environment (TOE) framework is used in this study to evaluate the variables affecting SMEs' digital transformation. The degree and efficacy of digital marketing adoption are influenced by organizational competencies, technological preparedness, and external market dynamics. Results show that SMEs that use new digital technologies, like automation and AI-driven analytics, see an increase in customer engagement and market share. By showing that SMEs may achieve sustainable business growth and competitive advantage by aligning their plans with organizational adaptability, technical advancements, and favorable environmental conditions, the study emphasizes the significance of a balanced approach across all TOE aspects. The findings give SMEs a road map for utilizing digital marketing to improve long-term success and business performance. The findings contribute to a deeper understanding of AI's capabilities, presenting a strategic roadmap for integrating these technologies into digital marketing ecosystem to achieve sustainable growth in the digital age. Using a random sampling technique, 450 respondents were selected from the 500 SMEs in the study area. Of the completed questionnaires, almost 90% were recovered and deemed valuable for the data analysis. The results of the study indicated that significant portion of SMEs (52%) generated between 2 and 4 million Naira in revenue after implementing AI-driven digital marketing, which is more than they did in the year before digital marketing automation was put into place.
Keywords: Technology; Organization; Environment; Digital Marketing; E-Commerce; SMEs; Social Media; Information Communication Technology; Artificial Intelligence